1995
DOI: 10.1111/j.1464-410x.1995.tb07422.x
|View full text |Cite
|
Sign up to set email alerts
|

Psychological reactions in men screened for prostate cancer

Abstract: In screening programmes for prostate cancer it is important to define clearly the high-risk groups to minimize the risk of adverse psychological reactions in those subjects with a low risk of having the disease. The results also emphasize the need to reduce the number of false positive results by choosing diagnostic tests of high specificity. The interval between a test and informing the subject of the results should be minimized to decrease the duration of the increased emotional stress.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
50
0

Year Published

2002
2002
2014
2014

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(54 citation statements)
references
References 19 publications
4
50
0
Order By: Relevance
“…In the Rotterdam PSA screening study, state anxiety levels (STAI) were highest among those who had undergone a biopsy, but had not yet received the results. 11 Gustafsson et al 21 measured serum cortisol as a biological marker for stress at various points during the investigation of men undergoing screening for prostate cancer. They found that the highest levels were found in men who had undergone a prostate biopsy, but were not informed of the result.…”
Section: Discussionmentioning
confidence: 99%
“…In the Rotterdam PSA screening study, state anxiety levels (STAI) were highest among those who had undergone a biopsy, but had not yet received the results. 11 Gustafsson et al 21 measured serum cortisol as a biological marker for stress at various points during the investigation of men undergoing screening for prostate cancer. They found that the highest levels were found in men who had undergone a prostate biopsy, but were not informed of the result.…”
Section: Discussionmentioning
confidence: 99%
“…3 About 20% of men undergoing to prostate biopsy felt anxious and/or highly stressed prior to the biopsy. 16 Pain, evaluation for possible malignancy and rectal route used by the probe are some possible reasons of the anxiety.…”
Section: Discussionmentioning
confidence: 99%
“…They found that patients undergoing screening experience emotional stress, resulting in elevated plasma cortisol levels. 3 Before a medical or surgical procedure, patients should be provided with sufficient information so that levels of anxiety are diminished. [4][5][6][7][8][9][10] However, the ideal way of providing this information is unclear.…”
Section: Introductionmentioning
confidence: 99%
“…A blood test to measure PSA is considered the most effective test currently available for the early detection of prostate cancer, but this effectiveness has also been questioned due to risks of false positives and false negatives. 10 A study on anxiety in prostate carcinoma suggests that while screening for prostate carcinoma, anxiety levels vary plausibly over the clinical timeline in response to stress and uncertainty both before to testing and while awaiting the reports. Baseline levels of anxiety related to screening are much lower for older men than younger men with the illness.…”
Section: General Psychological Issues In Prostate Cancermentioning
confidence: 99%